PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING DALAM PEMBELAJARAN MENULIS TEKS PERSUASI PADA PESERTA DIDIK KELAS VIII SMP NEGERI 1 TUNJUNGAN TAHUN PELAJARAN 2018/2019 - Sabila Aulia Rosyada; Asropah Asropah; Murywantobroto Murywantobroto (Universitas Ngudi Waluyo, 2020)
Application of the Contextual Teaching and Learning Model in Learning to Write Persuasive Texts in Students of Class VIII of SMP Negeri 1 Tunjungan in the 2018/2019 Academic Year. Thesis. Faculty of Language and Arts Education, University of PGRI Semarang. Advisor 1 Dr. Asropah, M.Pd. and Pembing II Drs. Murywantobroto, M.Hum. July 2019. The purpose of this study was to describe the application of the Contextual Teaching and Learning (CTL) model in learning to write persuasive texts in grade VIII students of SMP Negeri 1 Tunjungan in the 2018/2019 academic year. Data collection methods used in this study were technical tests and non-tests. The test technique is in the form of writing persuasion texts in writing according to the theme, structure, language rules and correlations between paragraphs. Whereas the nontest technique is in the form of an observation sheet of learning activities of teachers and students and questionnaires. The approach used is descriptive qualitative. The population in this study were all students of class VIII. The sample in this study was class VIII B, amounting to 31 participants. The technique of presenting the results of the data analysis was done qualitatively by analyzing the application of the Contextual Teaching and Learning model in learning to write persuasive texts to students of class VIII of SMP Negeri 1 Tunjungan. The results obtained in learning to write persuasion text using the Contextual teaching and Learning model can be applied in learning to write persuasion text in class VIII of SMP Negeri 1 Tunjungan in the 2018/2019 school year. The ability of students to write persuasion texts gets good grades. Students can write persuasion texts by analogizing the themes that have been determined. Thus, students can pour ideas freely. This can be seen from the average value of students reaching 88, the highest value of 100, and the lowest value of 76.Keywords: application, Contextual Teaaching and Learning model, writing persuasion texts